Analisis Simulasi Numerik Defleksi Balok Baja ST60 dengan Variasi Pembebanan dan Tumpuan - Muhammad Syaiful Fadly; Mustafa; Muhammad Ikram Kido; Muhammad Ghazali Arrahim (P3M Politeknik Negeri Cilacap, 2024)
This research aims to analyze the deflection that occurs through numerical simulation using Ansys Software in static structural modeling on an ST 60 steel square beam. The variables in this study are loads of 10, 15, and 20 N, as well as the types of supports, namely fixed-fixed, fixed-roller, and hinge-roller. The results show that the larger the load, the greater the deflection that occurs. The maximum deflection occurs at a load of 20 N. The fixed-fixed and hinge-roller supports show maximum deflection at a distance of 400 mm, while the fixed-roller support shows maximum deflection at a distance of 450 mm. Among the three types of supports used in this study, the simple support (hinge-roller) results in greater deflection compared to the fixed-fixed and fixed-roller supports. The hinge-roller support results in a deflection of 1.212 mm, the fixed-roller support results in a deflection of 0.541 mm, and the fixed-fixed support results in a deflection of 0.302 mm..